Prevalence of Diabetes Mellitus, Prediabetes and Its Associated Factors in Dessie Town, Northeast Ethiopia: A Community-Based Study - Endris, Toyba (Diabetes Metab Syndr Obes, 2019)
BACKGROUND: Diabetes mellitus is becoming an epidemic public health problem in developing countries such as Ethiopia. As the International Diabetes Federation indicates, the number of adults living with diabetes globally has been increasing from time to time. If early screening and follow-up are done, diabetes is a manageable disease. However, diabetes study at the community level in Ethiopia is limited and scarce. Therefore, the present study was conducted to assess the current prevalence of DM, prediabetes and its associated factors in Dessie Town, Northeast Ethiopia. METHODS: A community-based cross-sectional study was conducted from January to March 2019 among people aged 18 years and above in Dessie Town, Northeast Ethiopia. A multistage sampling technique was used to select a total of 587 study participants. Sociodemographic and behavioral characteristic data were collected using a pretested semi-structured questionnaire. Venous blood samples were used to determine the level of blood glucose and lipid profile. Diagnosis and classification of diabetes mellitus and prediabetes were based on the criteria of the American Diabetes Association. RESULTS: The prevalence of diabetes mellitus and prediabetes was 6.8% (95% CI 4.9–9.0) and 15.7% (95% CI 12.9–18.7), respectively. The prevalence of previously undiagnosed diabetes mellitus was 72.5%. Positive family history of diabetes mellitus (AOR: 20.24, 95% CI 4.74–86.43), smoking habit (AOR: 12.12, 95% CI 2.30–63.73), overweight (AOR: 21.95, 95% CI 6.73–71.603), systolic hypertension (AOR: 4.61, 95% CI 1.09–19.50) and hypercholesterolemia (AOR: 8.97, 95% CI 2.05–39.23) were significantly associated with diabetes mellitus. Prediabetes was associated with advanced age (AOR: 3.55, 95% CI 1.16–10.79), marital status (single) (AOR: 3.06, 95% CI 1.40–6.67), educational status (illiterate) (AOR: 2.35, 95% CI 1.04–5.35) and overweight (AOR: 2.11, 95% CI 1.05–4.23). CONCLUSION: There was a higher prevalence of diabetes mellitus and prediabetes. In addition, the prevalence of undiagnosed diabetes mellitus was high in our study area. Therefore, targeting the control and prevention strategy to such modifiable risk factors associated with diabetes and prediabetes may contribute to the reduction of the prevalence and further complications of diabetes mellitus.